2021
DOI: 10.1080/03079457.2020.1869698
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antigenic variant infectious bursal disease virus strains identified in South Korea

Abstract: Infectious bursal disease (IBD) is one of the most important immunosuppressive diseases of young chickens, causing considerable economic losses to the poultry industry. More than 30 years ago, an antigenic variant (av) pathotype of the IBD virus (IBDV) was reported to originate in, and subsequently spread among, poultry farms in the USA. Recently, a novel avIBDV lineage was identified in China and was shown to exhibit clear differences in its pathogenicity as well as molecular characteristics compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…The phylogenetic trees based on the nucleotide sequences of the polyprotein in Segment A showed that Serotype I strain contained four previously described genogroups: A1 (cIBDV), A2 (VarIBDV), A3 (vvIBDV), and A8 (aIBDV) [ 8 ]. Genogroup A2 included lineages A2a/b/c (early variant IBDV) and A2d (nVarIBDV) [ 8 , 18 ]. The IBDV-JS19-14701 strain was clustered with SHG19 [ 16 ], which is a representative strain of nVarIBDV (A2d) ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The phylogenetic trees based on the nucleotide sequences of the polyprotein in Segment A showed that Serotype I strain contained four previously described genogroups: A1 (cIBDV), A2 (VarIBDV), A3 (vvIBDV), and A8 (aIBDV) [ 8 ]. Genogroup A2 included lineages A2a/b/c (early variant IBDV) and A2d (nVarIBDV) [ 8 , 18 ]. The IBDV-JS19-14701 strain was clustered with SHG19 [ 16 ], which is a representative strain of nVarIBDV (A2d) ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…The HLJ0504-like IBDVs (A3B3) are the main prevalent strains with high pathogenicity, which have been threatening the poultry farming in China for nearly 30 years [ 9 , 10 , 11 , 12 ]. Such type of IBDVs have also been circulating in the neighboring countries including Pakistan [ 11 , 14 ], India [ 15 ], Bangladesh [ 38 ], Thailand, Vietnam [ 39 ], and Korea [ 18 ], and were also reported in Venezuela [ 30 ]. Recently, the widespread of nVarIBDV (A2dB1) was discovered in China [ 16 , 40 ] and also reported in Japan [ 17 ], Korea [ 18 ], and Malaysia [ 19 ] in succession.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations